Pengembangan Aplikasi Jual Beli Sampah Daur Ulang Menggunakan Framework Multiplatform - Ragil Saputra, Ardi; Mulyani, Yessi (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2023)
Environmental pollution caused by waste is increasingly worrying if there is no effort to overcome it. The lack of behavior in managing recyclable waste in society is one of the biggest factors in waste pollution in Indonesia. There are many recycling waste management facilities in Indonesia, but the location of waste management facilities is unevenly distributed, and there are price differences at each location, making the community less interested in managing recyclable waste. In this study, a buying and selling system for recyclable waste was developed based on Android devices as a buying and selling tools and a web application for managing user buying and selling data. The focus of this research is to build a buying and selling system for recyclable waste by integrating a multi-platform framework, namely using the Laravel framework for the web admin side and using the Flutter framework for the android application side. Then, to analyze the review of the users for the android application, this study used the System Usability Scale (SUS). The result of this study is an Android-based buying and selling application for recyclable waste and a web admin application for managing the data of the Android application. From the SUS analysis, the application obtained a score of 70, which is acceptable, with the note that the application built is already good, but still needs to be improved for transactions using an electronic wallet (e-wallet).